2022
DOI: 10.1109/tits.2021.3113787
|View full text |Cite
|
Sign up to set email alerts
|

Digital Twins in Unmanned Aerial Vehicles for Rapid Medical Resource Delivery in Epidemics

Abstract: The purposes are to explore the effect of Digital Twins (DTs) in Unmanned Aerial Vehicles (UAVs) on providing medical resources quickly and accurately during COVID-19 prevention and control. The feasibility of UAV DTs during COVID-19 prevention and control is analyzed. Deep Learning (DL) algorithms are introduced. A UAV DTs information forecasting model is constructed based on improved AlexNet, whose performance is analyzed through simulation experiments. As end-users and task proportion increase, the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…MRI examination uses high-resolution 1.5 T MR imager (SIEMENS MAGNETOM Symphony). The spin echo sequence is used in the sagittal T1 weighted picture, whereas the fast spin echo sequence and fat suppression sequence are used in the T2 weighted picture [ 27 ]. All X-ray examinations showed that the vertebral body was osteoporotic with some vertebral body height loss, and some vertebral body compression fractures showed wedge-shaped deformation [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…MRI examination uses high-resolution 1.5 T MR imager (SIEMENS MAGNETOM Symphony). The spin echo sequence is used in the sagittal T1 weighted picture, whereas the fast spin echo sequence and fat suppression sequence are used in the T2 weighted picture [ 27 ]. All X-ray examinations showed that the vertebral body was osteoporotic with some vertebral body height loss, and some vertebral body compression fractures showed wedge-shaped deformation [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cluster analysis is widely used in nursing-related research, and clinical research focuses on the clinical symptoms of diseases to understand the symptom clusters of various diseases and provide targeted interventions in clinical nursing work. Empirical evidence is used in the teaching and education management of nursing students, which is conducive to the setting and arrangement of students' courses; when used in nursing research, it can provide direction for the development trend of nursing specialty research [ 16 ]. However, in our country, cluster analysis is mainly applied to the visualization analysis of the literature and the metrological analysis of various fields of nursing to reveal the current research trends and focus and to discover the weak areas of current research and grasp the latest developments in nursing research.…”
Section: Application Of Machine Learning Algorithmsmentioning
confidence: 99%
“…According to the current medical big data background, the hierarchical improved clustering algorithm [ 16 ] is more suitable for scientific and efficient operating room nursing recommendation applications because the hierarchical clustering algorithm requires fewer prerequisites and a hierarchical nested tree.…”
Section: Application Of Machine Learning Algorithmsmentioning
confidence: 99%
“…It directly affects people's lives and realizes the connected living 5 . Moreover, the IoT offers a diversity of applications that are very beneficial in people's daily lives, such as smart cars, 6 home appliances, 7 security purposes, 8,9 healthcare monitoring, 10,11 intelligent logistics, 12 wearable devices, 13 weather monitoring, 14 and so on. On the other hand, the IoT has some issues such as privacy and security that prevent the successful implementation of its applications 15 .…”
Section: Introductionmentioning
confidence: 99%